2022
DOI: 10.1108/jfbm-09-2021-0112
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the spider's web: an investigation of dysfunctional behavioural patterns in a family firm

Abstract: PurposeDrawing on the theory of goal systems applied to family business this case study focuses on the interdependence between non-economic goals and family goals, in order to identify if and how achieving non-economic goals generates dysfunctional behavioural patterns for family members in the long term.Design/methodology/approachThis study used an inductive, 20-year longitudinal case-study based methodology.FindingsThis case study shows how the business family faces ethical/affective dimensions, struggling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…On the other hand, research has also shown that family members can also have a potentially negative effect on the firm: protected by their family affiliation, their lack of competencies, skills or misaligned values go unnoticed or unsanctioned (Kidwell et al, 2012). Moreover, the achievement of noneconomic goals can occur to the detriment of family goals, such as by generating a dysfunctional system, specifically in business family adaptability (Ferrari, 2022). Family business literature justifies this absence of (economic) sanction via the concept of "socio-emotional wealth" or "SEW."…”
Section: Roots: the Originsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, research has also shown that family members can also have a potentially negative effect on the firm: protected by their family affiliation, their lack of competencies, skills or misaligned values go unnoticed or unsanctioned (Kidwell et al, 2012). Moreover, the achievement of noneconomic goals can occur to the detriment of family goals, such as by generating a dysfunctional system, specifically in business family adaptability (Ferrari, 2022). Family business literature justifies this absence of (economic) sanction via the concept of "socio-emotional wealth" or "SEW."…”
Section: Roots: the Originsmentioning
confidence: 99%
“…On the other hand, research has also shown that family members can also have a potentially negative effect on the firm: protected by their family affiliation, their lack of competencies, skills or misaligned values go unnoticed or unsanctioned (Kidwell et al ., 2012). Moreover, the achievement of noneconomic goals can occur to the detriment of family goals, such as by generating a dysfunctional system, specifically in business family adaptability (Ferrari, 2022). Family business literature justifies this absence of (economic) sanction via the concept of “socio-emotional wealth” or “SEW.” SEW explains that family businesses can prioritize the welfare of the family over that of the economic performance of the firm: here turning a blind eye on the lack of competencies of a family member, to the detriment of organizational efficiency (see Smajić et al ., 2022 for a recent review).…”
Section: Roots: the Originsmentioning
confidence: 99%
“…The economic impact of the pandemic was particularly severe within the micro, small, and medium tourism enterprises (MSMTEs) as they have lost seven times more income than MSMEs in non-tourism sectors (International Finance Corporation, 2020). MSMEs are the most widespread type of enterprise in the world with profound economic and non-economic impacts, especially at the grassroots level of society (Ferrari, 2022). Particularly within the tourism sector, around 80% of enterprises are MSMEs, which employ a substantial percentage of women and young people (UNWTO, 2020).…”
Section: Introductionmentioning
confidence: 99%